THE EFFECT OF MATERNAL ANEMIA ON THE ANTHROPOMETRIC MEASUREMENTS IN FULLTERM NEONATES - Al-hajjiah, Nasma N; A Almkhadree, Mohammed (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The current study was performed to understand the effect of maternal anemia and its severity on anthropometric measurement of full-term neonates. Methods: In this study, 254 pregnant women were involved in this study. The women with anemia were classified depending on the hemoglobin concentration into three groups of mild (10.9â€“9.0 g/dl), moderate (8.9â€“7.0 g/dl), and severe anemia (Ë‚7.0 g/dl). The anthropometric measurements of the newborns were measured including birth weight, length, and head and chest circumference. Mothers with chronic diseases, preterm neonates, postdate neonates, neonates with congenital anomalies, or critical illnesses had been excluded from the study. Results: A total of 147 (58%) mothers had normal hemoglobin levels, and 107 (42%) mothers were anemic. The newborns were 123 males and 131 females. From the anemic mothers, 59 (55%) neonates had low weight, and 48 (45%) neonates had normal weight. In mothers with mild anemia (n=83), 40 (48%) neonates had low weight. In mothers with moderate anemia (n=21), 16 (76%) neonates had low weight. In mothers with severe anemia (n=3), all of their neonates had low weight. The current study revealed a statistically significant difference (p=0.002) in the anthropometric measurement of the full-term neonates between anemic and non-anemic mothers. There was also a statistically significant difference (p=0.001) in the anthropometric measurement of the full-termed neonates between severely and mildly anemic mothers. Conclusion: The current study shows that maternal anemia affects the anthropometric measurements of newly delivered full-term neonates. Neonates born to anemic mothers had low birth weight and shorter length than those in neonates who were born to non-anemic mothers.